Devaki Jain and Diane Elson (eds). Harvesting Feminist Knowledge for Public Policy. Sage Publications Pvt. Ltd. 20 II. 396 pages. US$ 43.26. (The Pakistan Development Review, 2011)
Harvesting Feminist Knowledge for Public Policy comprises 14 articles by feminist thinkers from all over the world, reflecting on problems of current patterns of development and calls for political, economic, and social changes to promote equality. In general the articles are about the "triple crises" of food, fuel, and finance and draw on the diversity of socioeconomic experiences of women in different countries. The authors argue for new ways of thinking about development, and offer ideas for reformulating development to secure social, economic, and political justice